COVID-19 AND ITS CONSEQUENCES ON HUMAN AND ANIMAL HEALTH (The Research of Medical Science Review, 2024)
This review analyzes the diverse effects of the COVID-19 pandemic on human and animal health, highlighting the zoonotic transmission of SARS-CoV-2, interruptions in veterinary services, and the significance of animal models in investigating long-term immune responses and chronic conditions such as Long COVID. This review examines the role of human-wildlife interactions in the zoonotic spillover of SARS-CoV-2 and assesses the impact of pandemic limitations on veterinarian treatment and animal welfare. This analysis examines recent research to underscore the issues encountered by veterinary services during the pandemic, including decreased surveillance and impaired disease management skills, as well as broader ramifications for animal welfare. The utilization of animal models, including hamsters and non-human primates, to examine viral persistence and immune responses has been addressed, highlighting their significance in formulating therapeutic strategies for humans and animals. This review highlights substantial deficiencies in existing knowledge, particularly regarding the long-term consequences of COVID-19 in animals and the inconsistent data on zoonotic reverse transmission. This study synthesizes these data and makes recommendations for future research, specifically aimed at improving a health approach that integrates human, animal, and environmental health to reduce future zoonotic threats. This thorough investigation provides significant insights into pandemic preparedness, highlighting the necessity for interdisciplinary teamwork to tackle global health issues